Strategies to enhance HIV Pre-Exposure Prophylaxis uptake and retention amongst young females at Gauteng province - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2023)
Thesis (PhD (Nursing Science))--University of Pretoria, 2022.